Historical Singularity and Alternative Representations of the Hundred Years' War in the Fate/Grand Order Game - Muhammad Rezky Noor Handy; Ahmad Aulia Rahman; Pidi Mohamad Setiadi (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2025)
The growing popularity of video games as a means of historical representation has significantly changed how people understand and experience the past. This study analyzes alternative representations of the Hundred Years' War (1337–1453) in the video game Fate/Grand Order, with a focus on the figure of Joan of Arc and the narrative construction of the concept of